Wpływ ćwiczeń rozciągających na wartości uzyskiwane w 6-minutowym teście marszowym wśród osób zdrowych = The effect of stretching exercises on the results obtained in the 6-minute walk test among healthy individuals - Janusz Kocjan (Kazimierz Wielki University, 2016)
Kocjan Janusz. Wpływ ćwiczeń rozciągających na wartości uzyskiwane w 6-minutowym teście marszowym wśród osób zdrowych = The effect of stretching exercises on the results obtained in the 6-minute walk test among healthy individuals. Journal of Education, Health and Sport. 2016;6(9):539-545. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.154754 http://ojs.ukw.edu.pl/index.php/johs/article/view/3879         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 21.09.2016.       WPŁYW ĆWICZEŃ ROZCIĄGAJĄCYCH NA WARTOŚCI UZYSKIWANE W 6-MINUTOWYM TEŚCIE MARSZOWYM WŚRÓD OSÓB ZDROWYCH   THE EFFECT OF STRETCHING EXERCISES ON THE RESULTS OBTAINED IN THE 6-MINUTE WALK TEST AMONG HEALTHY INDIVIDUALS   Janusz Kocjan   Studium Doktoranckie Wydziału Lekarskiego w Katowicach, Śląski Uniwersytet Medyczny w Katowicach Doctoral Studium of School of Medicine, Medical University of Silesia, Katowice, Poland   STRESZCZENIE             Celem pracy była ocena wpływu ćwiczeń rozciągających na rezultaty uzyskiwane w 6-minutowym teście marszowym (6MWT) wśród osób zdrowych. Badaniem objęto 40 pracowników biurowych u których nie występowały żadne schorzenia przewlekłe, których losowo przydzielono do jednej z dwóch grup: badanej (wykonującej ćwiczenia rozciągające przez okres 2 miesięcy) oraz kontrolnej (nie wykonującej ćwiczeń rozciągających, lecz kontynuujących dotychczasową aktywność). Średnie wartości uzyskane podczas wyjściowego 6MWT wyniosły odpowiednio: grupa badana: 584,61 ± 75,84 metrów, vs grupa kontrolna: 601,22 ± 80,95 metrów. W grupie badanej nie zaobserwowano istotnych statystycznie różnic pod wpływem wykonywanych przez okres 2 miesięcy ćwiczeń rozciągających na wartości odnotowane w 6MWT, jak również parametry krążeniowo-oddechowe. Brak zależności dotyczył również grupy kontrolnej.   SUMMARY             The aim of the study was to evaluate the effect of stretching exercises on the results achieved in the 6-minute walk test (6MWT) among healthy individuals. The study included 40 office workers without chronic diseases, who were randomly assigned to one of two study groups (performing stretching exercises for 2 months) and a control (not performing stretching exercises, but continuing the daily phydical activity). The mean values obtained during the initial 6MWT were, respectively: the study group: 584.61 ± 75.84 meters, vs the control group: 601.22 ± 80.95 meters. In the study group, there was no statistically significant difference after two months period of stretching exercises to the value recorded in the 6MWT, as well as cardio-respiratory parameters. No relationship was also noted in the control group.   Słowa kluczowe: test 6-minutowy, 6-MWT, ćwiczenia rozciągające. Key words: 6-minute walk test, 6-MWT, stretching exercises.